2016
DOI: 10.1038/srep32957
|View full text |Cite
|
Sign up to set email alerts
|

Nedd4-2 haploinsufficiency causes hyperactivity and increased sensitivity to inflammatory stimuli

Abstract: Nedd4-2 (NEDD4L in humans) is a ubiquitin protein ligase best known for its role in regulating ion channel internalization and turnover. Nedd4-2 deletion in mice causes perinatal lethality associated with increased epithelial sodium channel (ENaC) expression in lung and kidney. Abundant data suggest that Nedd4-2 plays a role in neuronal functions and may be linked to epilepsy and dyslexia in humans. We used a mouse model of Nedd4-2 haploinsufficiency to investigate whether an alteration in Nedd4-2 levels of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…Previous studies have demonstrated increased formalin-induced inflammatory pain in Nedd4-2 heterozygotes compared to wild-type (76,79), aligning with these findings for ciguatoxin inducedspontaneous pain as both results show reduction in NEDD4-2 activity is associated with greater pain sensitivities. The mechanism for increased nociception is hypothesised to be due to diminished NaV recycling in the absence of Nedd4-2 and a resultant increase in membrane excitability and pain transmission.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Previous studies have demonstrated increased formalin-induced inflammatory pain in Nedd4-2 heterozygotes compared to wild-type (76,79), aligning with these findings for ciguatoxin inducedspontaneous pain as both results show reduction in NEDD4-2 activity is associated with greater pain sensitivities. The mechanism for increased nociception is hypothesised to be due to diminished NaV recycling in the absence of Nedd4-2 and a resultant increase in membrane excitability and pain transmission.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, this hypothesis was not proven by measuring the expression of NaVs in the DRG for Nedd4-2 KO mice, which leaves room for additional experimentation to define the microscopic effects of NEDD4-2 on DRG channel populations through methods such as tissue straining or immunofluorescence. The effects of NEDD4-2 on DRG NaV channels is still uncertain, with one study showing that complete knockout of Nedd4-2 in nociceptive neurones caused an increase in the concentrations of both NaV1.7 and 1.8 (76), while another was unable to demonstrate changes in NaV1.7 and 1.8 levels in the DRG using incomplete knockout mice (79). This may suggest that reduced levels of Nedd4-2 in incomplete knockout models is not substantial enough to cause changes in NaV concentrations, and changes can only be seen with complete knockouts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NEDD4L is a HECT E3 ubiquitin ligase with multiple substrates regulating, among others, neuronal functions (Ekberg et al, 2014;Yanpallewar et al, 2016;Todaro et al, 2018). NEDD4L is highly expressed in the cortical plate, the ventricular zone, and the ganglionic eminences in the fetal brain of mice (Broix et al, 2016).…”
Section: Introductionmentioning
confidence: 99%